Supplier selection approach for competitive advantage (Research, Society and Development, 2022)
The objective of this article is to propose a procedure for the selection of suppliers by the criterion of competitive advantage based on the model of competition fields and weapons (CAC in Portuguese) and to present the functionality of an artifact (self-instructional software) built to facilitate the realization of this task by the contracting company. This software, which is configured in a technological product, is the result of a project financially supported by National Council for Scientific and Technological Development – CNPq (Brazil) under the Productivity Scholarship in Technological Development and Innovative Extension Program and can be freely accessed at https://supplier.camposearmas.com.br. This is a new criterion that leads the company to contract the supplier that best leverages its competitive advantages. If the company intends to obtain a competitive advantage, for example, in product quality, it must contract the supplier that has the best quality in the production process. The supplier to be selected is the one whose internal competencies are most aligned with the competitive strategy of the contracting company. In the article, it is shown that the competition field and weapons model is the appropriate theoretical framework to support the proposed supplier selection process and implemented by the software.